Stephen Ackroyd and Paul Thompson (2022). Organisational Misbehaviour - Karlsson, Jan Ch. (Nordic Journal of Working Life Studies, 2022)
It started with an article with the ingenious title ‘All quiet on the workplace front?’. Here, Paul Thompson and Stephen Ackroyd (1995) criticized the dominant types of analyses of work organizations in British working life studies of that time. In these studies, they pointed out that workers had disappeared as agents of workplace life, which was the quiet to which they alluded. According to much of the sociology of work, management had succeeded not only in subjecting workers to total control, but also in turning them into self-controlling dopes of company cultures. Already in Thompson and Ackroyd’s critique, we find concepts such as misbehavior, recalcitrance, and appropriation of time and products – concepts that are further theorized in the first edition of their book Organisational Misbehaviour (OMB, Ackroyd & Thompson 1999). Throughout, the authors emphasized the importance in workplace life of employees’ collective agency through informal self-organization. Undoubtedly, this is the most important book in the field in the beginning of the 2000s and it had a huge influence on working life studies. The success of the book meant that many have been waiting for a long time for a second edition – and now it is here.